2004
DOI: 10.1126/science.1092550
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Augments GABAergic Transmission in the Central Amygdala via CRF1 Receptors

Abstract: The central amygdala (CeA) plays a role in the relationship among stress, corticotropin-releasing factor (CRF), and alcohol abuse. In whole-cell recordings, both CRF and ethanol enhanced gamma-aminobutyric acid-mediated (GABAergic) neurotransmission in CeA neurons from wild-type and CRF2 receptor knockout mice, but not CRF1 receptor knockout mice. CRF1 (but not CRF2) receptor antagonists blocked both CRF and ethanol effects in wild-type mice. These data indicate that CRF1 receptors mediate ethanol enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
243
3
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(276 citation statements)
references
References 23 publications
24
243
3
4
Order By: Relevance
“…These results suggest that the anxiolytic properties of ethanol in the elevated plus maze are not regulated by opioid receptor systems within CeA or BLA nuclei of the amygdala. This is surprising since ethanol increases GABA release, GABA A receptor function (Roberto et al, 2003), GABAergic neurotransmission (Nie et al, 2004), and c-fos expression in GABAergic neurons (Morales et al, 1998) in the CeA. These results are also somewhat discrepant with previous reports from this lab (Wilson et al, 2003); however, some important technical differences between the previous report and the current study warrant discussion.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the anxiolytic properties of ethanol in the elevated plus maze are not regulated by opioid receptor systems within CeA or BLA nuclei of the amygdala. This is surprising since ethanol increases GABA release, GABA A receptor function (Roberto et al, 2003), GABAergic neurotransmission (Nie et al, 2004), and c-fos expression in GABAergic neurons (Morales et al, 1998) in the CeA. These results are also somewhat discrepant with previous reports from this lab (Wilson et al, 2003); however, some important technical differences between the previous report and the current study warrant discussion.…”
Section: Discussioncontrasting
confidence: 99%
“…Another potential problem is that ethanol is known to affect several neurotransmitter systems including GABA (Roberto et al, 2003), glutamate (Lovinger et al, 1989), neuroactive steroids (Sanna et al, 2004), and a variety of neuropeptides including opioids (de Gortari et al, 2000) and CRF (Nie et al, 2004). Therefore, even if opioid receptors modulate GABA A receptor function in the amygdala, the ability of ethanol to affect other neurotransmitter and neuromodulatory systems may be sufficient to circumvent any opioid receptor effects on GABA A receptor function localized selectively within the CeA or BLA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wan et al (1996) found that IPSCs from CA1 pyramidal cells were only sensitive to ethanol enhancement in the presence of a GABA B antagonist, providing a mechanism for the variability reported (see subsequent section on GABA B receptor influences). In another brain region, investigators (Nie et al, 2004;Roberto et al, 2003) reported that ethanol enhanced IPSCs from amygdaloid neurons.…”
Section: In Vitro Examination Of Ethanol Action On Gaba a Receptor Fumentioning
confidence: 99%
“…Subsequently, Roberto et al (2003Roberto et al ( , 2004a provided evidence that ethanol enhanced the effect of stimulusinduced GABA-mediated IPSPs and mIPSCs from neurons in slices from the central nucleus of the amygdala and caused release of GABA into microdialysatesFclear evidence that ethanol could facilitate GABA release. This action of ethanol to release GABA can apparently be modified at presynaptic sites (see designation in Figure 4), by GABA B (Ariwodola and Weiner, 2004;Wan et al, 1996) and corticotrophin releasing factor (CRF; Nie et al, 2004) receptors. Additionally, other neurotransmitter receptors affected by ethanol can influence neural circuits that influence GABA transmission (Carta et al, 2003(Carta et al, , 2004; Figure 3 Effect of ethanol on neural rate from cerebellar Purkinje neurons.…”
Section: Hypothesis For the Gabamimetic Profile Of Ethanolmentioning
confidence: 99%